2012
DOI: 10.1371/journal.pone.0046781
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Renovascular Damage in Zucker Diabetic Fatty Rat by NWT-03, an Egg Protein Hydrolysate with ACE- and DPP4-Inhibitory Activity

Abstract: BackgroundDipeptidyl peptidase 4 (DPP4) and angiotensin-converting enzyme (ACE) are important target enzymes in glycemic control and renovascular protection. Here, we studied the effect of NWT-03, an egg protein hydrolysate with DPP4- and ACE-inhibitory activity, on renovascular damage in Zucker diabetic fatty (ZDF) rats. Comparisons were made to rats treated with vildagliptin (VIL), included as a positive control for the effect of DPP4 inhibition.MethodsZDF rats received NWT-03 (1 g/kg/day) or VIL (3 mg/kg/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 41 publications
5
41
0
Order By: Relevance
“…Although ZDF animals displayed both an increase in non-fasting blood glucose levels and HbA 1c , it should be noted that the development of overt diabetes was considerably slower in this batch of ZDF than observed in our previous experiments in the same animal strain [68]. While the reason for this remains elusive, in view of the current data, the animals would be best defined as being pre-diabetic.…”
Section: Discussionmentioning
confidence: 63%
“…Although ZDF animals displayed both an increase in non-fasting blood glucose levels and HbA 1c , it should be noted that the development of overt diabetes was considerably slower in this batch of ZDF than observed in our previous experiments in the same animal strain [68]. While the reason for this remains elusive, in view of the current data, the animals would be best defined as being pre-diabetic.…”
Section: Discussionmentioning
confidence: 63%
“…Western blot was performed as described previously [23]. Briefly, after protein concentrations were determined (BCA Protein Assay Kit, Sigma-Aldrich), 50 µg protein lysates were separated via a 10% SDS-PAGE and transferred onto polyvinylidene difluoride membranes (Sigma-Aldrich, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that DPP-4 inhibitors exert beneficial effects on renal morphology and function in rodent diabetes models. [4][5][6][7][8] These renal effects have been demonstrated mostly in studies investigating hyperglycemic conditions. It is well known that the antidiabetic effects of DPP-4 inhibitors are mediated via increases in levels of the incretin hormones glucagon-like peptide (GLP)-1 and glucosedependent insulinotropic polypeptide (GIP).…”
mentioning
confidence: 99%